Non-Keynesian Effects of Fiscal Consolidations in Central Europe in the years 2000-2013 - Adam P. Balcerzak; Elzbieta Rogalska (Institute of Economic Research (IER), 2015)
Last two decades were a period of significant discussion concerning determinants of effectiveness of fiscal policy. After some cases of expansionary episodes of fiscal consolidations in eighties of XX century, an intensive international research on the possibility of non-Keynesian effects of fiscal contractions in highly developed countries has started. The aim of the article is to analyze the possibility of obtaining non-Keynesian effects of fiscal consolidations in post-transformation countries of Central Europe. An important aim of macroeconomic policy in the analyzed economies is to benefit the advantages of convergence process. Thus, the empirical analysis is made within conditional ß-convergence framework. The verification of hypothesis of ß-convergence enables to identify the long term tendency of output per capita, in the same time it enables to identify non-Keynesian effects of fiscal prudence and to assess their role in the process of reducing GDP gap between the analyzed economies. Then the potential transmission channels for non-Keynesian effects of fiscal policy were analyzed. In the research the data from Eurostat and European Commission for the years 2000-2013 was used. The paper provides arguments in favor of the existence of non-Keynesian effects of fiscal consolidations in Central Europe that support the process of conditional convergence.
Keywords: H3; 330; fiscal policy; fiscal consolidations; non-Keynesian effects; ß-conditional convergence; Central Europe